Magnetic resonance imaging of COVID-19 anosmic patients reveals abnormalities of the olfactory bulb: Preliminary prospective study. Issue 5 (November 2020) - Chetrit, Annaelle; Lechien, Jerome R.; Ammar, Amine; Chekkoury-Idrissi, Younes; Distinguin, Lea; Circiu, Marta; Saussez, Sven; Ballester, Marie-Christine; Vasse, Marc; Berradja, Najete; Hans, Stephane; Carlier, Robert; et al.
Highlights: COVID-19 patients with total loss of smell have more olfactory bulb abnormalities at the magnetic resonance imaging than patients without loss of smell. The olfactory bulb MRI abnormalities may be objectified through a signal intensity ratio measurement that is calculated between the average signals of the olfactory bulb and the frontal white matter. The loss of smell is probably due to olfactory bulb inflammation related to virus spread.